Validasi Paket Teknologi Budi Daya Padi (Oryza sativa) Lahan Rawa secara Intensif - Sujinah, Sujinah; Agustiani, Nurwulan; Gunawan, Indra; Margaret, Swisci (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2020)
An intensive swampland rice technology package, dubbed as RAISA, consisted of water and land management, swampland specific variety, population density bio-fertilizer, soil ameliorant, inorganic fertilization, integrated pest management, and use of mechanization. Validation of RAISA’s technology was aimed to determine technology components which significantly affected yield increase. The experiment was conducted at Karang Agung Experimental Station and farmer’s field in Banyuasin, South Sumatera, using a Randomized Complete Block Design with seven treatments and four replications. The treatments consisted of RAISA minus specific variety (P1), RAISA minus optimum plant population (P2), RAISA minus bio-fertilizer (P3), RAISA minus soil ameliorant (P4), RAISA minus inorganic fertilizer (P5), RAISA full package (P6), and farmer’s crop cultivation technique as control (P7). Result showed that the variety affected significantly on plant height, and plant population affected the number of tillers. The RAISA technological package increased rice yield by 41% compared to that of farmer practice. The RAISA technological components that significantly increased rice yield are variety, plant population, and soil ameliorant. RAISA is considered feasible to be applied with an R/C ratio of 1.57-1.97.